Hubungan Antara Adiksi Media Sosial dan Social Comparison Terhadap Kecenderungan Body Dissatisfaction Mahasiswi Pengguna Tiktok - Denok Surya Intan; Dhani, Dhini Rama (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2025)
This study aims to examine the relationship between social media addiction and social comparison on the tendency of body dissatisfaction in female TikTok users. The phenomenon of body dissatisfaction, which relates to dissatisfaction with the body, can be influenced by external factors such as social media. This study uses a quantitative method with a scale as a data measurement tool, involving 107 female college students as respondents. The results showed that there was a significant positive relationship between social media addiction and social comparison with body dissatisfaction, with contributions of 22.4% and 31.3%, respectively. Regression test shows that social media addiction and social comparison together affect body dissatisfaction by 37.4%. This study is in line with previous research which found that the intensity of social media use and the tendency to compare oneself with others can increase body dissatisfaction. Based on these results, it is expected that female students can be wiser in using social media and improve self-perception in order to avoid body dissatisfaction. This study also suggests that future research consider other factors that can affect body dissatisfaction.